Analysis Of Factors Affecting Poverty In The Province Of North Sumatra - Ulyah Masni, Naily (Al-Adzkiya Publisher, 2025)
The aim of this study is to conduct a descriptive economic analysis of the development of poverty levels in Indonesia during 2012–2022, to conduct a descriptive economic analysis of poverty trends in North Sumatra Province during 2012–2022, and to estimate the factors influencing poverty in North Sumatra Province. The analytical methods used include descriptive analysis and econometric modeling. The results of this study indicate that poverty in North Sumatra Province is relatively fluctuating and changes rapidly from year to year. With a large population, the proportion of poor people in the province is also significant. Several factors influence poverty, including population growth, Human Development Index (HDI), Gross Regional Domestic Product (GRDP), and unemployment. The estimation results from the econometric model show a positive correlation and are in line with the research hypothesis, where the variables of poor population, GRDP, HDI, and unemployment collectively and significantly influence poverty growth in North Sumatra Province by 100%.